Characteristics of First-Class Democracies The Role of Political and Economic Factors - . Ozan ÖRMECİ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Democratic regimes have some common characteristics and differences. These characteristics might be also understood as necessary prerequisites for countries that want to establish first-class developed democracies. This article aims to analyze common characteristics of firstclass democracies in the world in terms of per capita income, population, location, dominant religious affiliation, education level and basic principles of the state.